The assassination of Jesse James by the coward Robert Ford - Dominik, Andrew; Pitt, Brad, 1963-; Gardner, Dede; Scott, Ridley; Daly, Jules; Valdes, David; Affleck, Casey, 1975-; Hansen, Ron, 1947-; Warner Bros. Pictures (1969- ); Virtual Studios; Scott Free Productions; Plan B Entertainment; et al. (United States : Warner Bros. Pictures, 2007)
Recounts the last months of Jesse James's life, from meeting Robert Ford, a 19-year-old who idolizes Jesse, to the day Ford shoots him.
Copyright Claimant: Virtual Studios LLC. Warner Bros. Entertainment Inc. Pre-existing Material: Novel entitled "The assassination of Jesse James by the coward Robert Ford" by Ron Hansen. Screenplay entitled "The assassination of Jesse James by the coward Robert Ford" by Andrew Dominik. Certain sound recordings, musical compositions, and publications. Basis of Claim: Motion picture, including audio, visual, and other cinematographic material. Date of Creation: 2007; Date of Publication: September 21, 2007; Registration Number / Date: PA0001590837 / 2008-01-04.
Summary adapted from Internet movie database, viewed Mar. 25, 2008.
Based on the novel by Ron Hansen.
Not viewed.
Sources used: copyright database; Variety Web site, review posted Aug. 31, 2007, viewed Mar. 25, 2008; Internet movie database, viewed Mar. 25, 2008; FirstSearch, OCLC 182585178, viewed Mar. 25, 2008.
Executive producers, Brad Grey, Tony Scott, Lisa Ellzey, Benjamin Waisbren ; camera, Roger Deakins ; editing, Dylan Tichenor, Curtiss Clayton ; music, Nick Cave, Warren Ellis.
Keywords: James, Jesse, -- 1847-1882 -- Drama; Ford, Robert, -- 1862-1892 -- Drama; Assassination -- Drama; Criminal behavior -- Drama; Biographical -- Feature; Western -- Feature; Adaptation -- Feature